Continuous improvement model to increase productivity using lean manufacturing tools in an SME in the plastics industry - Vicuña Valera, Bruno Marcelo (2024)
Nowadays, companies face strong competition worldwide, so there is great pressure to increase productivity and reduce production costs. Low productivity is reflected in a high amount of waste, unproductive times, and returns in the extrusion process of an SME in the plastics industry. Therefore, a model focused on continuous improvement is proposed to increase productivity using Lean Manufacturing tools such as Standard Work, SMED, and TPM. Through a simulation of the extrusion process using the Arena software, it was possible to validate an increase in the productivity of the extrusion process by 4.97%, going from 0.21 to 0.22. Likewise, the Standard Work tool reduced wastage by 30.44%, the SMED tool reduced extruder machine setup times by 9.76%, and finally, the TPM tool, focused on its fourth pillar of quality maintenance, was able to reduce defective products by 28.38%.